Disaster Management using Internet of Things - Mrs. Saranjeet Kaur (International Journal of Advanced Science and Technology, 2020)
Natural disaster is a major challenge to the operation of a community or civilization that involves serious life, properties, financial or environmental tragedy & Affects that overwhelm the willingness of the person or civilization affected to use their own resources to cope with it.Experts are now documenting incidents, disasters for even moreResearchers have been studying accidents for our century now, & surveys of tragedy for nearly 40. There are a few mechanisms that form the ties in the chain when addressing crisis response, which operate in unison to fulfill the life cycle of emergency response.This process will start with risk assessment, preparedness for disasters, emergency management, resource distribution, reaction readiness and, lastly, recovery from disasters.Luckily, IoT has the answer to assist the organizations in the control of disasters at any level.